Optimal Monetary Policy under Rigid Wages and Decreasing Returns - Britta Kohlbrecher (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper is the first to study optimal Ramsey monetary policy in a search and matching model that combines real wage rigidity and decreasing returns to scale in production. Adding decreasing returns to scale significantly reduces the trade-off between employment and inflation stabilization usually associated with real wage rigidity. As firms adjust employment in response to an aggregate productivity shock, the resulting change in the marginal product of labor partly offsets the effect of a rigid real wage on marginal costs. The effect is quantitatively important. Optimal inflation volatility is reduced by a factor of four compared to a model with constant returns.
Keywords: E24; E52; J64; 330